Discursive Agency and Literary Visibility: Deconstructing Patriarchal Oppression and Re-narrating Female Subjectivity in Wafa Faith Hallam’s The Road from Morocco (2012) - Tahboun, Abdelhafid (International Journal of Language and Literary Studies, 2025)
Over centuries, mutely inhibited Moroccan women have been held captives of two oppressive yet mutually collusive narratives: one is religiously conservative and locally patriarchal, the other is hegemonically Eurocentric. Through delving into the feasible prospects of discursive agency and literary visibility, this paper explores the theme of deconstructing patriarchal oppression and re-narrating female subjectivity in Wafa Faith Hallam’s The Road from Morocco (2012). To trace the liberating potential of writing and probe its rewards of cultural activism and social emancipation, particular focus is put on the unruly contumacy evinced by Saadia, Wafa’s mother. This interpretive study re-examines how literary writing is reconfigured as a politically subversive practice of epistemological disobedience aimed to unsettle the patriarchal logic. To demonstrate the transformative power of literary writing as a sign of spectacular resistance, this reading invokes intersectionality theory and postcolonial feminism as profound theoretical and conceptual lenses. The paper concludes that Moroccan women’s literature often culminate in paradigm-shifting rearrangements in the cultural politics of male/female power imbalances. Hence, the symbolic power of Moroccan women’s writings resides not only in challenging national patriarchal orders and Orientalist circulations but also in transforming the gender-exclusive model of his-story to the gender-inclusive perspective of her-story.